India’s AIDS response: the missing voices of persons with disabilities - Singh, Satendra (Research and Humanities in Medical Education, 2015)
India has the third largest number of people living with HIV in the world. The UNAIDS Gap report has identified twelve risk groups that are especially vulnerable and have been left behind from the national AIDS response. Of these twelve, one is persons with disabilities. Disability is both a public health issue and a human rights issue; persons with disabilities are the world’s largest minority. Low awareness, sexual abuse, and lack of access to health services are the major reasons for people with disabilities being vulnerable. While the gap report is a landmark report, in that it compartmentalizes the risk groups, disability cannot be looked at in isolation. Since any of the other risk groups may include persons with disabilities, the issue is a complex one meriting greater attention. The National AIDS Control Organization has completely ignored this group of persons. To efficiently close the gap, an integrated and disability-inclusive HIV response is needed so that people with different types of disabilities, their caretakers, healthcare professionals and society are empowered to fight the collective battle against HIV/AIDS.